Review: antibiotic residues in meat, a public health problem in Colombia - Jaimes-Dueñez, Jeiczon; Ramírez-Villamizar, Luis Horacio; Barragán-Díaz, Ciro Alfonso; Cárdenas, Enrique; Niño Bayona, José Vicente (Spei Domus, 2022)
The use of antibiotics in animal production has represented great advantages for production systems, guaranteeing the control of infectious diseases that affect the productive capacity of animals, as well as their use as growth promoters. The presence of residues of these drugs in foods of animal origin, especially in meat is consider by world organizations for food safety and security as a risk factor that can affect public health, especially in the case of antibiotics, due to the subsequent resistance they generate. In addition, they are consider a barrier to the economic development of any country due to the limitations on their ability to expand into international markets. The methods for the detection of these residues are increasingly sensitive, being important for countries like Colombia, where reform of regulations, control mechanisms, and the strengthening of technological capacity have been intensified given the especially importance by meat exportations. This review aims to expose the most important points regarding the presence of these residues in meat, including the current panorama of national and international legislation, as well as the results of research on the most common drugs that are found, their effect on human health and the most used methods for their detection
Keywords: cattle; detection; safety; drugs; growth promoter; food